Rumen models - Cruz, Gustavo D.; Millen, Danilo Domingues [UNESP]; Rigueiro, André Luiz Nagatani [UNESP] (Springer Nature, 2016)
When ruminants consume some sort of feed, especially forage, a part of the organic matter ingested returns to the mouth to be chewed, and then swallowed again (Russell 2002). Consequently, part of this feed is degraded by ruminal microorganisms, which produce short-chain fatty acids (SFCA) that will supply the energy requirements of the host; whereas the particles that were not degraded, especially those smaller than 1.18 mm, by pass to the omasum via reticular-omasal orifice. In general, the facts just described is what happens during the day as a result of feeding of ruminants; however, it’s needed to understand the fermentation dynamic of various feedstuffs, as well as their rate of passage through the rumen and nutritional implications related to animal performance.